2022
DOI: 10.53730/ijhs.v6ns5.10928
|View full text |Cite
|
Sign up to set email alerts
|

Study of midkine protein as prognostic marker for thyroid disease in Al-Najaf City

Abstract: Objectives: The aim of this study is to detection of various thyroid diseases in the early stages and their impact on the metabolic state of the body through the estimation of the Midkine by using ELISA method. Methadology: The current study was conducted on  45 patients  with thyroid disease was attending in endocrine and diabetic center in the Al-Sadder Teaching Hospital and Al-Hakim General Hospital in AL-Najaf Province, and 45 healthy person, the samples collected  during  the period from September 2021 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…The current findings are in line with the findings of numerous prior research, which found that midkine level concentration was considerably higher in the NDH group compared to the control (Jawad M & Hussein,A..H. 2022). and from complications for hypothyroidism-related cardiovascular disease, MK has been associated with a number of cardiovascular diseases, and many research investigations on cardiovascular diseases have found elevated MK expression.…”
Section: Discussionsupporting
confidence: 92%
“…The current findings are in line with the findings of numerous prior research, which found that midkine level concentration was considerably higher in the NDH group compared to the control (Jawad M & Hussein,A..H. 2022). and from complications for hypothyroidism-related cardiovascular disease, MK has been associated with a number of cardiovascular diseases, and many research investigations on cardiovascular diseases have found elevated MK expression.…”
Section: Discussionsupporting
confidence: 92%